Globalization, Income Distribution and Sustainable Development : A Theoretical and Empirical Investigation - Das, Ramesh Chandra, 1973-, author 623270; Emerald Publishing Limited (Online service) issuing body 646680 (Bingley, UK : Emerald Publishing Limited, 2020)
Globalization, Income Distribution and Sustainable Development: A theoretical and empirical investigation focuses on the impact of globalization on income distribution in a wider perspective and exploring the impact of globalization on sustainable development in a range of countries across the globe.